2018
DOI: 10.15376/biores.13.3.5065-5079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold plasma surface pre-treatment of wheat straw particles on straw board properties

Abstract: Effects of the plasma treatment were evaluated for particles from winter wheat stalks relative to the properties of particleboards manufactured from such treated particles. Using urea-formaldehyde adhesive, boards with a nominal density of 540 kg/m3 and a thickness of 6 mm were manufactured. Two degrees of plasma treatment were selected: cold plasma applied at atmospheric pressure by jet system, with a generator output voltage of 26.9 V and a current of 6.9 A; and in the second treatment, a maximum voltage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The higher moisture values in the rapeseed-based particleboards were because of the absence of paraffin and other hydrophobic additives in the adhesive mixture. The figure also showed a clear effect from the particle modification on the higher resulting moisture content of the boards; the disruption of surface layer of particles led to higher water uptake (Hýsek et al 2018). The differences between the moisture content of the boards at the end of the experiment were statistically significant (p < 0.01).…”
Section: Fig 2 Water Absorption Of the Specimens Immersed In Watermentioning
confidence: 89%
“…The higher moisture values in the rapeseed-based particleboards were because of the absence of paraffin and other hydrophobic additives in the adhesive mixture. The figure also showed a clear effect from the particle modification on the higher resulting moisture content of the boards; the disruption of surface layer of particles led to higher water uptake (Hýsek et al 2018). The differences between the moisture content of the boards at the end of the experiment were statistically significant (p < 0.01).…”
Section: Fig 2 Water Absorption Of the Specimens Immersed In Watermentioning
confidence: 89%
“…In addition, the fact that the particleboardspanels did not reach the optimal range of compaction ratio (Figure 7) may also have contributed to these results. Strategies such as plasma treatment of the particles (Hýsek et al, 2018a) and chemical and hydrothermal treatments (Hýsek et al, 2018b) have been suggested to achieve better bonding between the particles and, consequently, better mechanical performance.…”
Section: Mechanical Properties Of the Panelsmentioning
confidence: 99%
“…There is also a large range of thermal conductivity for the different raw materials and their additives, which is probably the most interesting performance for insulation materials. Figure 4 shows the bending strength of the found particle boards in literature [8][9][10][11][12][13][14][15][16][17][18][19]. It is clear that the bending strength of the different materials vary significantly from each other.…”
Section: Use Of Agricultural Residues In Building Materials (Literatu...mentioning
confidence: 99%
“…Overview of insulation batt materials made from ARW and their thermal conductivity (based on[8][9][10][11][12][13][14][15][16][17][18][19])…”
mentioning
confidence: 99%
See 1 more Smart Citation